Educação em tempo integral: possibilidades das práticas pedagógicas em educação física na Escola Estadual Professor José Jório em São João do Manteninha/MG - Carrijo, William Vieira (2025)
The study examined the relationships between the policy orientations of Full-Time Education (FTE) and the production of pedagogical practice in Physical Education (PE) at Escola Estadual Professor José Jório, asking to what extent the expansion of formative times and spaces translates into more qualified learning experiences. Integral education was adopted as the guiding horizon, articulating cognitive, socioemotional, cultural, and civic dimensions and dialoguing with recent educational policy guidelines (Nogueira; Carvalho, 2020; Brasil, 2024). In PE, we assumed a curricular perspective that treats movement practices as sociocultural phenomena and relies on criteria of access, participation, and progression to guide the selection and organization of learning experiences (Betti; Zuliani, 2021; Batista; Graça; Estriga, 2024). Methodologically, we employed a qualitative approach with bibliographic, documentary, and field research; data production involved non-participant direct observation, a questionnaire, and semi-structured interviews, and the analysis followed procedures of content analysis and thematic reflection (Bardin, 2016; Tracy, 2020; Braun; Clarke, 2021; Minayo, 2022). The results indicated a repertoire of possibilities consistent with integral education: systematic use of active methodologies (project based learning, station rotation, cooperative learning, peer tutoring, case study, and inquiry into effort/recovery), inclusive practices guided by clear criteria of participation and progression, integration of digital technologies (apps and body-monitoring instruments), and ethical-pedagogical mediations oriented toward democratic coexistence and a culture of peace (Batista; Graça; Estriga, 2024; Brasil, 2024; Betti; Zuliani, 2021). These findings suggest that extended time becomes expanded learning when formative purposes are explicit, content is intentionally selected, assessment is formative, and the cultural mediation of movement practices is consistent. Nonetheless, structural bottlenecks persist, such as insufficient infrastructure, a monoculture of activities, material constraints, and narrow understandings of the role of FTE, which strain the pluralization of experiences and demand investment policies and continuing education centered on teachers’ collaborative professional learning (Garcia; Vaillant, 2020; Nogueira; Carvalho, 2020). We conclude that PE within FTE, when anchored in a clear pedagogical project and supported by enabling policies, expands cultural repertoires, strengthens bonds, and enhances the meanings of learning and living together in everyday school life (Betti; Zuliani, 2021; Brasil, 2024).